Tools for Targeted Genome Engineering of Established Drosophila Cell Lines. - Cherbas, L.; Hackney, J.; Gong, L.; Salzer, C.; Mauser, E.; Zhang, D.; Cherbas, P. (Genetics, 2015)
We describe an adaptation of ?C31 integrase-mediated targeted cassette exchange for use in Drosophila cell lines. Single copies of an attP-bounded docking platform carrying a GFP-expression marker, with or without insulator elements flanking the attP sites, were inserted by P-element transformation into the Kc167 and Sg4 cell lines; each of the resulting docking-site lines carries a single mapped copy of one of the docking platforms. Vectors for targeted substitution contain a cloning cassette flanked by attB sites. Targeted substitution occurs by integrase-mediated substitution between the attP sites (integrated) and the attB sites (vector). We describe procedures for isolating cells carrying the substitutions and for eliminating the products of secondary off-target events. We demonstrate the technology by integrating a cassette containing a Cu(2+)-inducible mCherry marker, and we report the expression properties of those lines. When compared with clonal lines made by traditional transformation methods, which lead to the illegitimate insertion of tandem arrays, targeted insertion lines give more uniform expression, lower basal expression, and higher induction ratios. Targeted substitution, though intricate, affords results that should greatly improve comparative expression assays-a major emphasis of cell-based studies.